THE INFLUENCE OF WORK INTEREST AND COMPETENCY THROUGH JOB SATISFACTION ON THE PERFORMANCE OF PT EMPLOYEES. MAJOR BOX CREATION TANJUNG MORAWA NORTH SUMATRA - Aulia, Isna; Aisyah, Nur; Pratama, Ikbar (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
A decline in employee productivity often stems from suboptimal work performance, which can impact overall company efficiency. This study aims to evaluate employee performance at PT. Tanjung Morawa Megah Box, North Sumatra, by analyzing the effects of work interest, competence, and job satisfaction, along with their interactions. Utilizing a quantitative research approach, data analysis was conducted using the Structural Equation Modeling (SEM) method to examine relationships between these variables. The findings indicate that competence significantly influences employee performance, as evidenced by a significance level of 0.000 < 0.05. Similarly, work interest also has a significant and positive effect on performance, with a significance level of 0.002 < 0.05. Job satisfaction acts as a crucial mediating variable in linking competence and work interest to performance, with a significance level of 0.000 < 0.05. The interaction analysis further highlights that enhancing employee competence and fostering job satisfaction can strengthen the impact of work interest on performance. When combined, work interest, competence, and job satisfaction contribute significantly to employee performance, with the overall model showing a strong significance level of 0.000 < 0.05. These findings suggest that companies should focus on comprehensive training programs, employee motivation initiatives, and the development of a positive work environment. By prioritizing these aspects, organizations can enhance employee engagement and performance, ultimately driving business success and sustainability. Future research may explore additional factors such as leadership style, organizational culture, and career development opportunities to further refine strategies for improving workforce productivity.